EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, AND NET PROFIT MARGIN ON PRICE EARNING RATIO - Muhammad Ariq Naufal; Astrid Dita Meirina Hakim (Jurnal Scientia, 2023)
This research aims to show the effect of the Current Ratio, Debt to Equity Ratio, Return On Equity, and Net Profit Margin on the Price Earning Ratio. The data used are secondary data from the annual financial statements of the construction and building sub-sector listed on the Indonesia Stock Exchange for 2014-2018. This study uses purposive sampling with 10 (ten) companies listed on the Indonesia Stock Exchange used as samples. This study uses multiple linear regression analysis, tested using SPSS 20. The results of the research show that Return On Equity has a significant influence on Price Earning Ratio, Current Ratio has no significant influence on Price Earning Ratio, Debt to Equity Ratio has no significant influence on Price Earning Ratio, Net Profit Margin has no significant influence on Price Earning Ratio.